Visualization of Small Vessels by Micro–Computed Tomography Using Titanium Dioxide Nanoparticles as a Novel Contrast Agent - Taku Goto; Ruriko Tanabe; Hirotoshi Shibuya; Masaru Tamura; Shintaro Nomura (International Journal of Biomedical Imaging)
Angiography by means of micro–computed tomography (m-CT) is extensively used for the diagnosis of vasculature disorders. To establish a connection between m-CT images and genuine histopathology findings, we developed two novel titanium dioxide nanoparticle (TiO2-NP)–based perfusion contrast agents: TiNpCA-1 and TiNpCA-2. Three-dimensionally reconstructed m-CT images in mice perfused with these contrast agents showed high resolution and accuracy in various organs without deformation or dilation of vessels. Vessels<20  μm in diameter were clearly visualized by m-CT, and capillaries of 4 μm in diameter were visualized by nano-CT. After perfusion, the contrast agents were kept in the vessels by the formation of an aggregate with ethanol. Histological samples were prepared from CT-scanned specimens. No perfusion-induced damage or abnormal structures were observed. The signals of the contrast agents were detected clearly, and the tissue histology was of adequate quality for pathological diagnosis. Agglomerates of TiO2-NPs were present in both agents; their approximate sizes were 1.0 and 6.0 μm in TiNpCA-1 and 1.5 μm in TiNpCA-2. We considered that these agglomerates were trapped within capillaries at the beginning of perfusion. And at the end of perfusion, vessels of larger size were filled with agglomerates. These findings suggest a direct correlation between the signal intensity in m-CT imaging and the volume of contrast agent entering the vessels, indicating a quantitative aspect to the system. The low K-edge value of titanium (4.6 KeV) ensures that the signal intensity of the contrast agent remains unaffected at low energies (40 KeV). Lower energy levels improve the contrast-to-noise ratio. Consequently, using titanium dioxide as a contrast agent allows us to achieve a higher contrast-to-noise ratio while maintaining a favorable signal-to-noise ratio. Our results strongly support the notion that TiO2-NPs as a contrast agents hold promise not only for investigating circulatory disorders in experimental pathology but also for uncovering new insights in anatomical physiology.